SsT Decomposition Method For Solving Fully Fuzzy Linear System - Jaikumar, K.; Surya, S. (Institut Teknologi Bandung, 2013)
The SsT Decomposition method for solving of linear equations make it possible to obtain the values of roots of the system with the specified accuracy as the limit of the sequence of some vectors. In this topic we are going to consider vectors as fuzzy vectors. We have considered a numerical example and tried to find out solution vector in fuzzified form using method of SsT Decomposition.